Patient-partner engagement at the Centre de recherche du CHUS in the Province of Québec, Canada: from an intuitive methodology to outreach after three years of implementation - Boutin, Denis (Res Involv Engagem, 2021)
BACKGROUND: Medical societies and funding agencies strongly recommend that patients be included as partners in research publications and grant applications. Although this “top-down” approach is certainly efficient at forcing this new and desirable type of collaboration, our past experience demonstrated that it often results in an ambiguous relationship as not yet well integrated into the cultures of either patients’ or the researchers’. The question our group raised from this observation was: “How to generate a cultural shift toward a fruitful and long-lasting collaboration between patients and researchers? A “bottom-up” approach was key to our stakeholders. The overall objective was to build a trusting and bidirectional-ecosystem between patients and researchers. The specific objectives were to document: 1) the steps that led to the development of the first patient-partner strategic committee within a research center in the Province of Québec; 2) the committee’s achievements after 3 years. METHODS: Eighteen volunteer members, 12 patient-partners and 6 clinician/institutional representatives, were invited to represent the six research themes of the Centre de recherche du CHU de Sherbrooke (CRCHUS) (Quebec, Canada). Information on the services offered by Committee was disseminated internally and to external partners. Committee members satisfaction was evaluated. RESULTS: From May 2017 to April 2020, members attended 29 scheduled and 6 ad hoc meetings and contributed to activities requiring over 1000 h of volunteer time in 2018–2019 and 1907 h in the 2019–2020 period. The Committee’s implication spanned governance, expertise, and knowledge transfer in research. Participation in these activities increased annually at local, provincial, national and international levels. The Patient-Partner Committee collaborated with various local (n = 7), provincial (n = 6) and national (n = 4) partners. Member satisfaction with the Committee’s mandate and format was 100%. CONCLUSIONS: The CRCHUS co-constructed a Patient-Partner Strategic Committee which resulted in meaningful bilateral, trusting and fruitful collaborations between patients, researchers and partners. The “bottom-up” approach - envisioned and implemented by the Committee, where the expertise and the needs of patients complemented those of researchers, foundations, networks and decision-makers - is key to the success of a cultural shift. The CRCHUS Committee created a hub to develop the relevant intrinsic potential aimed at changing the socio-cultural environment of science.